Sulodexide Significantly Improves Endothelial Dysfunction and Alleviates Chest Pain and Palpitations in Patients With Long-COVID-19: Insights From TUN-EndCOV Study - Charfeddine, Salma; Ibnhadjamor, Hassen; Jdidi, Jihen; Torjmen, Slim; Kraiem, Salma; Bahloul, Amine; Makni, Ahmed; Kallel, Nesrine; Moussa, Nedia; Boudaya, Mariem; Touil, Imen; Ghrab, Aiman; et al. (Frontiers in Cardiovascular Medicine, 2022)
Abstract Objective: Non-respiratory long-COVID 19 symptoms are mainly related to a lasting endothelial dysfunction and microcirculation impairment. We hypothesized that Sulodexide, a purified glycosaminoglycan mixture with a beneficial endothelial effect in arterial and venous peripheral diseases, may be effective in a subset of long COVID-19 patients. Approach and results: We conducted a multicenter prospective quasi-experimental study. A subset of 290 patients from TUN End-COV study with long COVID-19 symptoms and endothelial dysfunction were included. The endothelial function was clinically assessed using a post-occlusive reactive hyperemia protocol with finger thermal monitoring device. Endothelial quality index (EQI) was assessed at inclusion and 21-days later. The study population was assigned to a sulodexide group (144 patients) or a no-medical treatment group (146 patients). Clinical characteristics were similar at inclusion in the two groups. Fatigue, shortness of breath and chest pain were the most common symptoms, respectively 54.5%, 53.8% and 28.3%. At 21-days, the sulodexide group improved significantly better than the no-medical treatment group in chest pain (83.7% vs 43.6%, p<10-3), palpitations (85.2% vs 52.9%, p=0.009) and endothelial function (median delta-EQI 0.66 (0.6) vs 0.18 (0.3); p <10-3). Endothelial function improvement was significantly correlated to chest pain and palpitations recovery (AUC = 0.66, CI [ 0.57- 0.75], p = 0.001 and AUC =0.60, CI[0.51- 0.69], p = 0.03) respectively. Conclusion: Sulodexide significantly improves long lasting post COVID-19 endothelial dysfunction and alleviates chest pain and palpitations.